ANALISIS FAKTOR RISIKO ERGONOMI PERAWAT TERHADAP KELUHAN MUSCULOSKELETAL DISORDERS - Indah, Vivi; Utami, Tri Niswati; Nuraini (Jurnal Keperawatan Priority, 2023)
Nurses are one of the medical staff who play an active role in improving health development. The purpose of this study was to analyze the risk factors of nurse ergonomics for complaints of musculoskeletal disorders in the inpatient room of Rumah Sakit Umum Langsa. This research is analytic observational research with a case-control design. The population in this study were all inpatient nurses at Langsa Hospital. The sample involved in this study was 144 nurses, consisting of 72 people as case samples and 72 people as control samples. The sampling was done by purposive sampling. Based on the results of the study, it was found that the age, tenure, and work position of nurses were related to complaints of musculoskeletal disorders (MSDs), where older nurses (36-50 years) and long working years tended to experience MSDs complaints, as well as nurses who worked in positionswork that is not ergonomic is more likely to experience MSDs. Meanwhile, the gender of the nurse is not related to complaints of musculoskeletal disorders (MSDs) because both women and men have the same risk of experiencing MSDs complaints. This study concludes that the most at risk for musculoskeletal disorders is the work position variable. It is recommended that the K3RS team develop and implement SOP (Standard Operating Procedures) regarding the risk of patient handling for nurses at work, and conduct training related to patient handling or ergonomics activities for nurses.